O canto que não cala: biossegurança e o direito à ritualização dos mortos. - Pereira, Dalva Chaves (2023)
The New Coronavirus Pandemic started in Asia and after a stopover of a few weeks in Europe landed in Brazil. One of the first people to die from Covid-19 may not even have had a passport, a black housemaid who was infected by her boss arriving from Italy. The black housemaid could not do social isolation, order food on the app, ride in cabs, she had to get infected by her mistress, who arrived from Italy and could not be without a maid. The disease that arrived in Brazil through the rich would massively kill the poorest. The pandemic brought another phenomenon, the non-ritualization of the dead. The main objective of this study was to understand how family members of Covid victims who were prevented from holding farewell funeral ceremonies would mourn. To this end, the qualitative approach enabled an investigation with new and varied perspectives, allowing a sensitive look at phenomena that could not be quantified. A broad bibliographic review was carried out about the conceptual fields of death and mourning, Covid and rituals, with the descriptors: mourning, ceremonial, "funeral ritual", pandemic and "political power". Twelve narrative interviews were conducted with people who had lost family members victimized by Covid-19, in videoconference format. For the treatment of the collected material, the Foucauldian-inspired Discourse Analysis was used, articulated with reflections on death and mourning in the writings of Phillipe Ariès mainly, followed by the philosophers Hannah Arendt, Judith Butler, and the philosophers Michel Foucault and Achile Mbembe, in the approaches to state violence and the right to mourn. The results showed that the impossibility of ritualizing and participating in posthumous ceremonies was mentioned by the participants as a routine that generates great suffering for the family. The studies that dealt with the theme of mourning include as a vitally important factor for the beginning of the mourning process, seeing the body of the deceased family member, verifying this passage. The study also showed that the adoption of biosafety burial management policies should be developed respecting groups and populations that have traditions that preserve ancestral burial practices, especially the native peoples. For Butler, the politics of violence and death determine which bodies can or cannot be mourned, and the research showed that populations in greater social vulnerability were directly and unrestrictedly affected by the effects of the pandemic. Besides getting sick, the lack of minimum conditions of protection and care contributed to an even greater distance between the socioeconomic conditions of the population.